PERAN STAKEHOLDERS DALAM PENGELOLAAN OBJEK WISATA ALAM SIWANG PARADISE DI DESA SIWANG KOTA AMBON - Fanny Soselissa; Billy Seipalla (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
The potential of the natural tourist attraction of Siwang Paradise will have a high attractiveness value if it is supported by the role of stakeholders in management and development. The purpose of this study is to analyze the role of stakeholders in the management and development of the natural tourist attraction of Siwang Paradise, and what obstacles are experienced by stakeholders in optimally managing and developing these objects. The method used is descriptive qualitative, the determination of respondents is based on snowball sampling technique, the analysis is carried out inductively based on facts and the results of interviews with respondents and key actors. The results showed that the stakeholders involved in the management of the Siwang Paradise object were the key actors (area owners) and the main actors (surrounding communities). Constraints in the management of the Siwang object are due to the lack of trust within the area owner to involve supporting stakeholders, in this case the private sector, NGOs, and academics. So that the management of objects in developing various readiness of tourist attraction products becomes slow and runs not optimally. The visible impact of the management is the economic impact, through increasing family income, social impact, reducing unemployment, opening up road access, making motorcycle taxis easier to use, making it easier for people to do their activities. While the ecological impact is the management is carried out by paying attention to the cleanliness of the environment from waste, and based on the carrying capacity of the object area.